SEVA3D: Autonomous Vehicles Parking Simulator in a three-dimensional environment - Heinen, Milton Roberto; Osório, Fernando Santos; Heinen, Farlei José; Kelber, Christian (INFOCOMP Journal of Computer Science, 2007)
This paper describes a simulation system proposed in order to study and to implement intelligent autonomous vehicle control. The developed system can automatically drive a vehicle, implementing a robust control system capable of simulating in a realistic way autonomous parking in a parallel parking space. The system controls the vehicles based on the reading of sonar sensors and automatically generates acceleration and steering commands, parking it in a parallel parking space. The controller was implemented using a rule-based nite state automaton, and the results obtained in our simulations demonstrated that the proposed controller is perfectly able to correctly park the vehicle in different situations.